The effectiveness of social media in the marketing of a selected commercial bank in the Western Cape, South Africa - Shumba, Richard Christopher (Cape Peninsula University of Technology, 2018)
The key objective of this study is to determine the effectiveness of social media as a banking communication tool for a selected commercial bank in the Western Cape, South Africa. A secondary objective is to measure bank users’ perceptions regarding the use of social media to market various banking products and portfolios. The study employs a confusion matrix design to collect and analyse data, combining quantitative and qualitative research methods to understand and address the research problem. An emerging understanding of integrated banking communication is the foundation on which this research is built. It provides a context for the study, and highlights the effectiveness and limitations of social media in banking. A review of the relevant SMBA affirmed the importance of the social media in banking, and provided the basis for a framework and approach to interactive banking. A comprehensive social media banking application (SMBa) could be designed in line with banking practices to create an enabling business environment. This could reinforce banking communication for South African banks and enable a tailor-made banking communication model aligned to social media, in order to develop a sharing-culture.
Thesis (MTech (Business Administration))--Cape Peninsula University of Technology, 2018.
Keywords: Banks and banking; Bank marketing; Online social networks; Social media; Internet marketing